MODEL PEMBELAJARAN MACCA SEBAGAI PENDEKATAN KONSTRUKTIVISTIK UNTUK PEMBELAJARAN EKOSISTEM YANG REFLEKTIF, KOLABORATIF, DAN KONTEKSTUAL - Sumarni; Muhiddin Palennari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Science learning in the 21st century requires strategies that can foster active thinking, reflective ability, collaboration, and contextual application of concepts. This article conceptually reviews the MACCA (Mindful Analysis, Collaboration, Creation, and Application) learning model as a constructivist approach grounded in the macca cultural values of the Bugis people in South Sulawesi. The macca value reflects wisdom, prudence, and careful reasoning, which align with the reflective character emphasized in ecosystem learning. This study employs a literature review method by examining various works related to constructivist theory, reflective and collaborative learning, as well as the integration of local wisdom in science education. The findings indicate that MACCA adapts Vygotsky’s principles of social constructivism to a local cultural context through four interconnected stages: Mindful Analysis, Collaboration, Creation, and Application. These four syntaxes create a learning process that is reflective, creative, collaborative, and applicative, contributing to the development of students’ critical thinking, social responsibility, and ecological awareness. Thus, the MACCA model not only offers a culture-based pedagogical innovation but also strengthens the linkage between constructivist theory and contextual learning practices in supporting the Merdeka Curriculum and the advancement of sustainable scientific literacy.